2016
DOI: 10.1080/19475411.2017.1278834
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dielectric and piezoelectric behavior of unpoled and poled barium titanate polycrystals with oxygen vacancies using phase field method

Abstract: This article studies the dielectric and piezoelectric behavior of unpoled and poled barium titanate (BaTiO 3 ) polycrystals with oxygen vacancies. A phase field model is employed for BaTiO 3 polycrystals, coupled with the time-dependent Ginzburg-Landau theory and the oxygen vacancies diffusion, to demonstrate the interaction between oxygen vacancies and domain evolutions. To generate grain structures, the phase field model for grain growth is also used. The hysteresis loop and butterfly curve are predicted at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…In this instance, the observations indicate that the main characteristics of the hysteresis loop, such as coercive field E c =0 .95 • 10 5 V/m and residual polarization P r =0.24 C/m 2 coincide with the data described in the literature (e.g., [29,54,56,59,60]).…”
Section: Simulation Of Ferroelectric Polarization Switching In Batio ...supporting
confidence: 85%
“…In this instance, the observations indicate that the main characteristics of the hysteresis loop, such as coercive field E c =0 .95 • 10 5 V/m and residual polarization P r =0.24 C/m 2 coincide with the data described in the literature (e.g., [29,54,56,59,60]).…”
Section: Simulation Of Ferroelectric Polarization Switching In Batio ...supporting
confidence: 85%
“…For example, this technique can give the most-rational designs by means of investigating the interaction mechanism of grain size [ 136 ] and oxygen activity [ 137 ] on the microstructures and properties of BaTiO 3 ceramics. Narita et al reported [ 138 ] a phase field simulation framework to study the effects of oxygen vacancy densities and grain size on the poling of the pristine BaTiO 3 polycrystals, as well as on the piezoelectric coefficient and the permittivity of the poled BaTiO 3 polycrystals. Additionally, phase field simulation [ 139 ] also can be introduced to study the intrinsic relationships between the grain size on the domain structures and the electromechanical properties of ferroelectric polycrystals.…”
Section: The Design Of the High-temperature Piezoelectric Materialsmentioning
confidence: 99%
“…The parameters of the computational experiments correspond to the experimental data described in [55]. In the tests, the parameters are set to be: the amplitude of the field intensity is E 0 =2.5 • 10 5 V/m, the field frequency is f = 50 Hz (ω =2π • f ), the gradient coefficient is ψ =5• 10 8 m 3 /F, the kinetic coefficient (which determines the velocity of movement of domain walls) is δ =2• 10 5 m•s/F [56]. The observation time is θ =0 .03 s, the characteristic time of the process is t ⇤ = 1 s, and the sample thickness is varied.…”
Section: Computational Experiments Setupmentioning
confidence: 99%